THE ROLE, ORIGIN, CLASSIFICATION, AND PRACTICAL APPLICATION OF PROBIOTICS IN VETERINARY MEDICINE - Burxonova S.A.; Doniyorov Sh. (Bright Mind Publishing, 2025)
This article provides information about the history, types, proper use, dosage, and storage conditions of probiotics.
Keywords: Pro bios, bacteria, Inoprobit, BioLack, VetLact, Protexin, Lactobacillus